Defective Expression and DNA Variants of TGFBR2 in Chinese Small Cell Lung Carcinoma - Zhao, ZhenHong; Xu, Jibin; Xie, Jun; Bao, Yang; Wang, Xiaotian; Wang, Lei; Wu, Junjie; Jin, Li; Xu, Zhiyun; Wang, Jiucun (IntechOpen, 2012)
None